Riboflavin in neurological diseases: therapeutic advances, metabolic insights, and emerging genetic strategies - Tao, Zhiming; Huo, Jinglu; Hao, Xiaosheng; Liang, Jianmin (Frontiers in Neurology, 2025)
BackgroundRiboflavin (vitamin B2), a precursor of flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD), is essential for mitochondrial function, redox balance, and neuronal viability. Impairments in riboflavin transport and metabolism contribute to a growing spectrum of neurological diseases.ObjectiveThis review provides a comprehensive update on the therapeutic applications, metabolic mechanisms, and gene-based strategies involving riboflavin in neurological disorders.MethodsWe systematically analyzed clinical and experimental studies published between 2012 and 2025, focusing on riboflavin-responsive conditions and molecular mechanisms relevant to neurological pathology.ResultsRiboflavin supplementation—particularly in high doses—has demonstrated substantial efficacy in conditions such as riboflavin transporter deficiency (RTD), multiple acyl-CoA dehydrogenase deficiency (MADD), and migraine. Emerging data suggest potential benefit in Parkinson’s disease, Alzheimer’s disease, multiple sclerosis, and acute brain injury. Mechanistically, riboflavin supports mitochondrial bioenergetics, antioxidant systems, and epigenetic regulation. Recent advances in gene therapy and pharmacological chaperones targeting riboflavin-dependent pathways offer promising therapeutic directions.ConclusionRiboflavin is evolving from a conventional micronutrient into a multifaceted therapeutic agent in neurology. Integration of gene-based approaches, targeted delivery systems, and biomarker-guided interventions may establish riboflavin as a key component of precision medicine strategies for neurological disorders.